2012
DOI: 10.1371/journal.pone.0035994
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Immune Complexes Shift the TLR-Induced Cytokine Production of Distinct Polarized Human Macrophage Subsets towards IL-10

Abstract: BackgroundCostimulation of murine macrophages with immune complexes (ICs) and TLR ligands leads to alternative activation. Studies on human myeloid cells, however, indicate that ICs induce an increased pro-inflammatory cytokine production. This study aimed to clarify the effect of ICs on the pro- versus anti-inflammatory profile of human polarized macrophages.Materials and MethodsMonocytes isolated from peripheral blood of healthy donors were polarized for four days with IFN-γ, IL-4, IL-10, GM-CSF, M-CSF, or L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 51 publications
10
35
0
Order By: Relevance
“…Moreover, importantly, our results are in very good accordance with a recent study showing that contrary to their widely accepted classification as anti-inflammatory M2 macrophages, human M-CSF-polarised macrophages promote inflammation, instead of having immunoregulatory properties upon co-stimulation by immobilised IgG and a toll-like receptor (TLR) ligand 32. These and the above-mentioned results,31 also obtained with immobilised IgG, suggest that the results we obtained with the immobilised ACPA-IC, that we chose to study because of their strong relevance to the RA pathophysiology, might be generalisable to all immobilised IgG containing IC. However, this remains to be demonstrated as the hierarchies of the inflammatory character of the cytokine response of the different macrophage subtypes obtained with other types of IC, formed with different or additional antibody isotypes, exhibiting a different solubility, or also including ligands for receptors of pathogen-associated molecular patterns, also remain to be investigated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, importantly, our results are in very good accordance with a recent study showing that contrary to their widely accepted classification as anti-inflammatory M2 macrophages, human M-CSF-polarised macrophages promote inflammation, instead of having immunoregulatory properties upon co-stimulation by immobilised IgG and a toll-like receptor (TLR) ligand 32. These and the above-mentioned results,31 also obtained with immobilised IgG, suggest that the results we obtained with the immobilised ACPA-IC, that we chose to study because of their strong relevance to the RA pathophysiology, might be generalisable to all immobilised IgG containing IC. However, this remains to be demonstrated as the hierarchies of the inflammatory character of the cytokine response of the different macrophage subtypes obtained with other types of IC, formed with different or additional antibody isotypes, exhibiting a different solubility, or also including ligands for receptors of pathogen-associated molecular patterns, also remain to be investigated.…”
Section: Discussionsupporting
confidence: 92%
“…More generally, this observation, made in a very simplified model, confirms the major influence of macrophage microenvironment on their functional properties. Finally, for IFN-γ-polarised, IL-4-polarised and IL-10-polarised cells, concerning the ACPA-IC-induced secretion of IL-6, TNF-α and IL-10 and the corresponding TNF-α:IL-10 ratio, the hierarchies between macrophages subsets matched with those reported for macrophages stimulated by immobilised IgG 31. However and interestingly, given their phenotypic classification as IL-10-like immunoregulatory macrophages, in comparison with other macrophage subsets, including the phenotypically alike IL-10-polarised cells, the M-CSF-treated cells produced the highest levels of pro-inflammatory cytokines and the ratio between their TNF-α and IL-10 secretions was similar to that produced by the IFN-γ-polarised cells.…”
Section: Discussionsupporting
confidence: 68%
“…Interference with the formation of the immunological synapse has substantial consequences for Ca 2+ -dependent cytoskeletal rearrangement, transcriptional regulation, and cytokine monocyte response by maintaining IFN ␥ in Th cells ( Fig. 2 ): IFN ␥ -polarized monocytes have been shown to preferably produce TNF-␣ and IL-6 in the presence of LPS ( 53 ). One group reported a negative association between the LPS-stimulated production of TNF-␣ and IL-6 by PBMC and n -3 PUFA intake, which, however, appeared to be characterized by a "U-shaped" dose-response relationship with IL-10 effects (reviewed in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…As a variety of TLRs, including TLR2, 4, 7 and 9 can engage immune complexes [2531], and CD44 can interact with TLR2 [34], TLR4 [35] and Myd88 [33], we next questioned whether the ameliorative abilities of IVIg or KM114 were reliant on Myd88 expression. The observation that anti-platelet antibody resulted in thrombocytopenia in Myd88 deficient mice suggests that, similar to TLR4, Myd88 expression is not required for the induction of thrombocytopenia in the murine ITP model.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that IVIg may form immune complexes to exert its ameliorative effects [24]. Although TLRs are classically thought of as receptors for pathogen-associated molecular patterns, it has been demonstrated that both soluble and insoluble immune complexes have the ability to engage various TLRs, and regulate inflammation [2531]. …”
Section: Introductionmentioning
confidence: 99%